Tackle injury epidemiology and performance in rugby league - narrative synthesis - Hendricks, S.; Jones, B.; Burger, N. (South African Journal of Sports Medicine, 2021)
Background: In rugby league (RL), the ability to repeatedly engage in the tackle, whether as a ball carrier or tackler, is essential for team success and player performance. It is also the leading cause of injury, with over 90% of total injuries occurring during the tackle in professional and amateur cohorts. To effectively reduce the risk of injury and optimise performance, establishing the extent of the `problem`, through injury surveillance or descriptive performance studies is required.